2008
DOI: 10.1038/ng.126
|View full text |Cite
|
Sign up to set email alerts
|

The mouse X chromosome is enriched for multicopy testis genes showing postmeiotic expression

Abstract: According to the prevailing view, mammalian X chromosomes are enriched in spermatogenesis genes expressed before meiosis1–3 and deficient in spermatogenesis genes expressed after meiosis2,3. The paucity of post-meiotic genes on the X chromosome has been interpreted as a consequence of Meiotic Sex Chromosome Inactivation (MSCI) – the complete silencing of genes on the XY bivalent at meiotic prophase4,5. Recent studies have concluded that MSCI-initiated silencing persists beyond meiosis6–8 and that most X-genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
335
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(359 citation statements)
references
References 21 publications
23
335
1
Order By: Relevance
“…Only 31% of ampliconic genes are shared with mouse compared with 95% for single-copy genes (24), showing a rapid turnover of these regions. In the mouse, these genes are expressed postmeiotically (25). The ampliconic regions show a striking concordance with low-diversity regions that are most strongly affected by selection in the species (Fig.…”
Section: Low-diversity Regions Associated With X-linked Ampliconic Rementioning
confidence: 63%
See 1 more Smart Citation
“…Only 31% of ampliconic genes are shared with mouse compared with 95% for single-copy genes (24), showing a rapid turnover of these regions. In the mouse, these genes are expressed postmeiotically (25). The ampliconic regions show a striking concordance with low-diversity regions that are most strongly affected by selection in the species (Fig.…”
Section: Low-diversity Regions Associated With X-linked Ampliconic Rementioning
confidence: 63%
“…We predict that the association should increase if the hypothesis is true. Direct expression analyses at different stages during spermatogenesis and individual differences may also reveal whether escape from meiotic sex chromosome inactivation (25) or interference with XY body formation is a source of meiotic drive.…”
Section: Discussionmentioning
confidence: 99%
“…Following meiosis, most single copy genes on the X and Y chromosomes remain in a transcriptionally silent state known as Post-meiotic Sex Chromatin (PMSC) [106], [101], [104], while genes present in multicopy arrays show expression in postmeiotic cells [107]. The role that PMSC plays in paternal inheritance in the early embryo is unknown.…”
Section: Box 2: Meiotic Sex Chromosome Inactivationmentioning
confidence: 99%
“…85 During postmeitotic spermatid development, the X and Y appear to remain globally repressed although a selected set of single-and multi-copy genes is (re)expressed. 84,[95][96][97] Recently, Cocquet et al 98 showed that the multicopy gene Sly is specifically required for the maintenance of postmeiotic X chromosome repression. In addition to SLY, the above-mentioned ubiquitin conjugating enzyme HR6B is also required for the maintenance of meiotic and postmeiotic sex chromosome inactivation.…”
Section: Detection and Silencing Of Nonhomologous Regionsmentioning
confidence: 99%